2007
DOI: 10.1130/b26088.1
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface seepage of seawater across a barrier: A source of water and salt to peripheral salt basins

Abstract: Many of the great Phanerozoic salt basins share a common paleogeography, in which a deep lake or sea is separated from the ocean by a narrow barrier. Examples include the Aptian evaporites of the South Atlantic rift basins and the Messinian salt deposits of the Mediterranean Sea and the North Caspian depression. Marine transgressions over the barrier have been proposed as the origin for saline conditions in these basins. We test an alternate hypothesis, that subsurface seepage of seawater through the barrier w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…On the other hand, Dupré et al (2007) found that subsidence trends derived from backstripping calculations from the South Gabon Basin could correlate with a syn-rift origin for the evaporites. Nunn & Harris (2007) also underlined that the thick underlying Barremian-lower Aptian section from both margins north of the Rio Grande Rise-Walvis Ridge contained an extensive record of deposition from saline lakes, with a complete absence of any marine signature from the Neocomian to the middle Aptian. These authors proposed a model of subsurface seepage of sea water across a barrier to explain this apparent geological dilemma, which also would constitute a possible additional mechanism for the syn-rift deposition of the great evaporite sequence.…”
Section: Depositional Environment and Origin Of The Salt Basinsmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, Dupré et al (2007) found that subsidence trends derived from backstripping calculations from the South Gabon Basin could correlate with a syn-rift origin for the evaporites. Nunn & Harris (2007) also underlined that the thick underlying Barremian-lower Aptian section from both margins north of the Rio Grande Rise-Walvis Ridge contained an extensive record of deposition from saline lakes, with a complete absence of any marine signature from the Neocomian to the middle Aptian. These authors proposed a model of subsurface seepage of sea water across a barrier to explain this apparent geological dilemma, which also would constitute a possible additional mechanism for the syn-rift deposition of the great evaporite sequence.…”
Section: Depositional Environment and Origin Of The Salt Basinsmentioning
confidence: 88%
“…The deposition of these units is characterized by a low tectonic activity without major block faulting (Marton et al 2000;Moulin et al 2005) and is related to the formation of offshore basins such as parts of the Gabon Basin (Tessereinc & Villemin 1990). The lacustrine sedimentation was followed by the deposition of a thin layer of marine sediments known as the Chela Layer (Moulin et al 2005;Nunn & Harris 2007). Most authors agree that the salt was deposited during Aptian time in about 5 Myr (Moulin et al 2005 and references therein).…”
Section: Descriptionmentioning
confidence: 99%
“…These features indicate that middleelate Aptian sag depocenters evolved to salt basins during the last synrift stage. Hypersaline conditions in deep lakes of the sag margin resulted from either seepage of seawater through the Walvis RidgeRio Grande Rise (Nunn and Harris, 2007), intermittent marine incursions over this structural barrier (Karner and Gambôa, 2007), or a combination of both processes. Based on the available seismic and well data it is not possible to determine the processes controlling salt precipitation.…”
Section: Aptian/albian Salt Deposition and Implications For The Hydromentioning
confidence: 99%
“…Lakes do not commonly contain forams, although some species may survive if introduced into coastal lakes or basins with near sea water salinities. Marine transgressions over the barrier, or subsurface seepage of seawater through the barrier have been proposed as the origin for saline conditions in these basins, and therefore a significant source of water, influencing both water level and water composition [30]. In addition to the river discharge a contribution of seawater at a coastal zone may lead to deposition of dissolved manganese and iron carried Table 7; where symbol m is the metal content in plant and m is the metal content in soil.…”
Section: Source For As and Heavy Metals At The Varnavas Limestone Quamentioning
confidence: 99%